Personal characteristics and strategic orientation among AIM micro-entrepreneurs - Wan Hussin, Wan Sabri; Hamdan, Hamdino (Kolej Universiti Polytech MARA Kuala Lumpur, 2015)
This is a conceptual paper to discuss some traits of AIM micro-entrepreneurs. The discussion will be pursued to answer the question of how their personal characteristics and their strategic mindset may contribute to their success through the research proposed. The micro-enterprise is the tool for micro-entrepreneurs to own and run the business to meet the needs of life and the introduction of new products and changes in the industry. Microfinance programs such as Amanah Ikhtiar Malaysia (AIM) is required to complement the relationship of micro-enterprise and entrepreneurship to enable micro-enterprise being carried out through the concept of entrepreneurship. Hence this study will attempt to provide a through understanding of how micro-entrepreneurs among AIM participants make strategic decision making under the competitive environment. This study will also try to see whether the performance of the business and the creation of business strategy is influenced by the personal characteristics of micro-entrepreneurs. This study will also look at whether the personal characteristics of the micro-entrepreneurs influenced their entrepreneurial orientation. In this case micro-entrepreneurs have a unique way to maximize the use of their own capabilities (human capital) to be brought into their business. The paper is proposing the methodology that will be employed for the purpose to achieve objectives mentioned.